2006
DOI: 10.1002/jemt.20364
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a thermoregulatory hot spot in the prothorax of the large carpenter bee and the bumble bee

Abstract: In both the large carpenter bee (Xylocopa pubescens) and the bumblebee (Bombus terrestris), a hot spot was detected in the center of the prothorax on its dorsal-external aspect. In both cases, the temperature in this hot spot was found to be greater than the ambient temperature and that at the tip of the gaster. In B. terrestris, it was higher by 9-10 degrees C from that at the gaster tip and by 15-16 degrees C from the ambient temperature, while in X. pubescens the corresponding differences were 11-20 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This difference may be due to differences in the geographical region, climate zone, and range of elevational gradient. A commonly reported pattern in species richness along elevational gradients is a unimodal distribution with a mid-elevation peak [20]. In our study, peak species diversity occurred at middle elevations due to the presence of two species (Apis dorsata and Xylocopa caerulea) that began to appear above 442 m asl.…”
Section: Discussionsupporting
confidence: 46%
“…This difference may be due to differences in the geographical region, climate zone, and range of elevational gradient. A commonly reported pattern in species richness along elevational gradients is a unimodal distribution with a mid-elevation peak [20]. In our study, peak species diversity occurred at middle elevations due to the presence of two species (Apis dorsata and Xylocopa caerulea) that began to appear above 442 m asl.…”
Section: Discussionsupporting
confidence: 46%
“…This heat tolerance suggests good heat regulation ability in carpenter bees, possibly controlled by a thermoregulatory center in the prothorax [51].…”
Section: Abiotic Requirements For Foragingmentioning
confidence: 83%
“…Not surprisingly, in ants we failed to detect a hot spot. Of the insects examined for a hot spot by us, we need point out the Vespa orientalis (Galushko et al, 2004;Ishay et al, 2006a,b;Plotkin et al, 2005) as well as the solitary bee, Xylocopa pubescens, and the social bee, Bombus terrestris (Volynchik et al, 2006), and in all of these, a hot spot was detected. Apart from us, other investigators have also reported the presence of a hot spot in various insects, like the honeybee Apis mellifera (Stabentheiner, 2001;Stabentheiner et al, 2002;Underwood, 1991) and the solitary bee Anthophora and other solitary bee species in New Guinea (Stone, 1993).…”
Section: Introductionmentioning
confidence: 99%